Literasi Digital Sebagai Upaya Mengatasi Sadfishing Penyalahgunaan Donasi di Aplikasi X - Calosa, Priya Gladys; Astari, Devi Wening (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
The rampant misuse of donation funds by a Semarang comedian, Singgih Sahara, has become a hot topic on social media, especially on the X application. Singgih provoked sympathetic responses from others by spreading excessive sad stories to attract netizens to donate to him, commonly called the sadfishing phenomenon. Using a case study method, this qualitative study aims to analyze the application of digital literacy in disclosing Singgih's sadfishing of donation funds on the X application. Data were collected through observation, online interviews with several related accounts, and documentation of discussion spaces by the @zoelfick account. The study shows that in disclosing the case of misuse of funds, Singgih has implemented seven of the eight elements of digital literacy proposed by Hague Payton, namely 1) functional skills, 2) creativity, 3) critical thinking skills, 4) social and cultural understanding, 5) collaboration, 6) skills in finding and selecting accurate, credible, and reliable information, 7) effective communication. Only one element has not been fulfilled, namely electronic security. It is hoped that more people will be aware of the importance of digital literacy in protecting themselves from the commodification of sadfishing cases on social media.